DOI: 10.31274/etd-180810-772
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial efficacy of phosvitin, carvacrol, or nisin alone or combined against foodborne human enteric pathogens

Abstract: CHAPTER 4. GROWTH INHIBITION OF STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI O157:H7 AND BACKGROUND MICROFLORA BY PHOSVITIN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 250 publications
1
11
0
Order By: Relevance
“…Several studies have demonstrated that carvacrol has both bacteriostatic and bactericidal activity against foodborne microorganisms, including Salmonella enterica (27,(73)(74)(75). The effectiveness of carvacrol as a natural antimicrobial compound is well established, and its mechanism of action is believed to be associated with structural and functional damage to cellular membranes (25,28,(75)(76)(77). It has also been previously demonstrated as an antibiofilm compound.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that carvacrol has both bacteriostatic and bactericidal activity against foodborne microorganisms, including Salmonella enterica (27,(73)(74)(75). The effectiveness of carvacrol as a natural antimicrobial compound is well established, and its mechanism of action is believed to be associated with structural and functional damage to cellular membranes (25,28,(75)(76)(77). It has also been previously demonstrated as an antibiofilm compound.…”
Section: Discussionmentioning
confidence: 99%
“…As more manufacturers formulated products with synthetic preservatives, consumers have raised the issue of potential negative health effects and have thus created a demand for naturally derived food additives and minimally processed foods (White, 2011). This consumer driven effort to push food manufacturers to replace chemical or synthetic ingredients with more natural ones is known as green consumerism.…”
mentioning
confidence: 99%
“…Phosvitin has an amino acid composition of 50% serine, and 90% of which are phosphorylated . It contains 216 amino acids of which 123 are serines (Fig 1;White, 2011;Byrne et al, 1984;.…”
Section: Compositionmentioning
confidence: 99%
“…The cost of phosvitin is $1,225.00 per gram based on the current price listed in the Sigma-Aldrich 2012 catalog. More recently, a water/ethanol based method, developed by researchers at Iowa State University, permits an efficient and cost effective option for extraction and purification of phosvitin from hens' egg yolk (White, 2011).…”
Section: Extraction Isolation and Purificationmentioning
confidence: 99%
See 1 more Smart Citation